Extraction and characterization of chitosan from dermal plates of the devil fish (Hypostomus plecostomus) - Amador-Mendoza, Adolfo; Juárez-Lopez, Rafael; Martínez-Galero, Nelda Xanath; García-Muñoz, Miguel Ángel; Palacios-Torres, Rogelio Enrique; Aguilera-Morales, Martha Elena (Ecosistemas y Recursos Agropecuarios, 2025)
The devil fish (Hypostomus plecostomus) is a highly invasive exotic species due to its remarkable adaptability and the significant ecological damage it causes in aquatic ecosystems. This research aimed to extract, characterize, and evaluate the chemical purification of chitosan from fish tegumental shields, comparing it with chitosan obtained from shrimp exoskeletons. The biopolymer was purified through acid-alkaline hydrolysis (0.6 M HCl/25°C/1h and 0.4 M NaOH/28°C/3h), deacetylation (40% NaOH/110°C/5.5h), and depigmentation (38% NaClO/28°C/0.15h). Desmineralization, deproteinization, color chart, insoluble content, degree of acetylation, molecular weight, Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), and scanning electron microscopy (SEM) were evaluated. Chitosans from shrimp exoskeletons and devil fish tegumental shields obtained deproteinization percentages of 98.91 and 97.67%, desmineralization of 98.19 and 97.95%, deacetylation percentages of 82.031 and 83.346%, and molecular weights (MW) of 112.934 and 206.507 kDa respectively. FT-IR results identified an absorption band corresponding to C=O stretching in both samples, indicating the presence of carboxylic anion (-COO). Thermograms showed lower degradation temperatures (308°C) for commercial chitosan compared to that from devil fish (324°C). Devil fish tegumental shields offer chitosan similar to commercial sources, with significant economic potential and a 25% yield, potentially controlling invasive populations and restoring ecosystems.
Keywords: Desmineralization; deproteinization; deacetylation